Pengelolaan Media Sosial Instagram Kementerian Energi dan Sumber Daya Mineral “@kesdm” Oleh Biro Klik - Farsya Aulia Putri (Lembaga Pengembangan Kinerja Dosen, 2024)
In maintaining its existence in the eyes of the public, the Ministry of Energy and Mineral Resources uses social media as a means to communicate, publish and promote its various products. Instagram is one of the social media used to disseminate information as well as build branding through interesting content. The aim of this research is to find out how the Instagram @kesdm social media owned by the Secretariat General of the Ministry of Energy and Mineral Resources (ESDM) of the Republic of Indonesia is managed by the Communications, Public Information Services and Cooperation Bureau (KLIK). The approach method used is an exploratory study. In implementing social media activation activities, the planning stage is the first discussion which begins with understanding the purpose of using the social media platform, the type of content to be posted and the target audience. Every time content is created, the social media team will create a content upload schedule or what is usually called Editorial Planning. . Furthermore, at the implementation stage, all types of content plans that have been created will be immediately executed. In the final stage, namely evaluation, the Instagram @kesdm social media team will create a monthly report as a form of accountability for the KLIK Bureau for all activities related to managing Instagram social media.